2019
DOI: 10.1519/jsc.0000000000002617
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation in Unilateral Barbell Exercises: Implications for Strength Training and Rehabilitation

Abstract: Mausehund, L, Skard, AE, and Krosshaug, T. Muscle activation in unilateral barbell exercises: Implications for strength training and rehabilitation. J Strength Cond Res XX(X): 000-000, 2018-The purpose of the present investigation was to assess lower-body muscle activity and hamstrings-to-quadriceps (HQ) activation ratios during performance of the split squat (SS), single-leg squat (SLS), and rear foot elevated split squat (RFESS), while using the same relative load and performing the exercises to muscular fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…However, it is not clear how hamstring recruitment during dynamic landing tasks can readily be increased and retained. Some studies have shown isometric strength or balance training is ineffective in increasing hamstring coactivity with the quadriceps [40,41], others suggest specific strength training can increase hamstring-quadriceps coactivation and potentially be beneficial in ACL injury prevention and rehabilitation [42]. Thus, the selection, intensity, and biofeedback of exercises might be important when focusing on ACL injury prevention, as has been suggested in literature [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear how hamstring recruitment during dynamic landing tasks can readily be increased and retained. Some studies have shown isometric strength or balance training is ineffective in increasing hamstring coactivity with the quadriceps [40,41], others suggest specific strength training can increase hamstring-quadriceps coactivation and potentially be beneficial in ACL injury prevention and rehabilitation [42]. Thus, the selection, intensity, and biofeedback of exercises might be important when focusing on ACL injury prevention, as has been suggested in literature [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although the BOSU-down condition created higher global instability, it offered a flat and rigid surface that compelled the participants to act differently in avoiding the knee valgus position. Although this study did not test this muscle, the role of the gluteus medius in stabilizing the posture can probably explain the lower activation of the vastus medialis in the BOSU-down [13,32,33] actions. Furthermore, the role of the biceps femoris co-contraction in the most unstable conditions seemed to be clear in a half-squat.…”
Section: Discussionmentioning
confidence: 83%
“…As reported in previous studies, the vastus medialis and lateralis achieved a higher, but non-significant, very-high activation during a 6-RM Bulgarian squat compared to the unstable Bulgarian squat [17]. The study conducted by Mausehund et al [54], in healthy and moderate strength-trained students, indicated that the activation of the vastus lateralis was higher, but not significant, for the 6-RM Bulgarian squat than for the 6-RM split squat and single-leg squat, even though both exercises registered a very high level of activity. These authors also showed non-significant differences for the gluteus medius while performing the Bulgarian squat and split squat, even though these two exercises provided a moderate activity of the gluteus medius.…”
Section: Discussionmentioning
confidence: 86%
“…Differently, the Bulgarian squat is more demanding than the standard lunge. Previous studies showed that the activity of the biceps femoris and vastus (medialis and lateralis) was very high [17,54] and that of the gluteus medius was moderate [54]. Thus, performing a Bulgarian squat with the front leg on the floor demands a higher hip and thigh muscle recruitment than a standard lunge, and therefore, the difference in the muscle activation between the traditional and suspended exercises is higher in case of a standard lunge than the Bulgarian squat.…”
Section: Discussionmentioning
confidence: 99%